2008
DOI: 10.2337/dc08-0898
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Risk Variables of Metabolic Syndrome Since Childhood in Pre-Diabetic and Type 2 Diabetic Subjects

Abstract: OBJECTIVE -That type 2 diabetes is associated with the metabolic syndrome is known. However, information is lacking regarding the long-term and adverse changes of metabolic syndrome variables in the development of type 2 diabetes from childhood to adulthood.RESEARCH DESIGN AND METHODS -Observations were examined, retrospectively, in a community-based cohort of normoglycemic (n ϭ 1,838), pre-diabetic (n ϭ 90), and type 2 diabetic (n ϭ 60) subjects followed serially for cardiovascular risk factors during childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 29 publications
9
71
0
2
Order By: Relevance
“…As such, investigations into the similarities and differences in pathological processes observed between children and adults are important, particularly if optimal therapy is to be implemented in childhood. A report from the Bogalusa Heart Study observed that adults who developed IGT or type 2 diabetes mellitus had higher glucose levels from childhood to adulthood compared with those adults who were normoglycaemic [12]. Also, a recent longitudinal study by Tirosh et al [5] reported that high NFPG levels constituted an independent risk factor for the development of type 2 diabetes mellitus within a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As such, investigations into the similarities and differences in pathological processes observed between children and adults are important, particularly if optimal therapy is to be implemented in childhood. A report from the Bogalusa Heart Study observed that adults who developed IGT or type 2 diabetes mellitus had higher glucose levels from childhood to adulthood compared with those adults who were normoglycaemic [12]. Also, a recent longitudinal study by Tirosh et al [5] reported that high NFPG levels constituted an independent risk factor for the development of type 2 diabetes mellitus within a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, before fasting glucose reaches the diagnostic range for IFG, impairments in the regulation of glucose homeostasis might already exist. Studies investigating the association between NFPG and the risk of cardiovascular disease (CVD) are limited in adults [3,11,12] and even more sparse in children [10]. The aim of the present study was to investigate whether NFPG levels in a large multiracial sample of obese children and adolescents could act as a marker of metabolic and cardiovascular deterioration.…”
mentioning
confidence: 97%
“…With respect to diabetes, white male-versus-white female subjects and black femaleversus-white female subjects have significantly higher prevalence. Male-versus-female subjects with prediabetes and black-versuswhite subjects with diabetes have a significantly higher prevalence [37,55]. Furthermore, African American children show a higher degree of clustering of long-term rates of change in MetS risk variables than observed in whites [41].…”
Section: Ethnic and Population Contrastsmentioning
confidence: 97%
“…This increase is partially attributable to an increased prevalence of obesity [35]. Pharmacological management is reserved for individuals with hypertension who do not respond to behavioral changes, and/or have additional cardiovascular risk factors such as diabetes [36] or even prediabetes [37].…”
Section: Screening For High Blood Pressure In Childrenmentioning
confidence: 99%
“…However, evidence indicates that people who develop diabetes in adulthood had higher body mass index (BMI) and subscapular skin fold as well as higher levels of glucose, triglycerides, and insulin, higher blood pressure, and lower levels of HDL-cholesterol (HDL-C) during childhood than those who do not develop diabetes [6]. Additionally, the American Pediatric Association suggests that cardiovascular risk factors be evaluated in children between 2 and 10 years of age when they have family history of cardiovascular diseases [7].…”
Section: Introductionmentioning
confidence: 99%